Comparison of endurance performance, spatiotemporal stride parameters and ground reaction forces in runners wearing traditional and minimalistic running shoes - Lichtenstein, E.; Donath, L.; Roth, R.; Oeri, A.; Faude, O. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Comparison of endurance performance, spatiotemporal stride parameters and ground reaction forces in runners wearing traditional and minimalistic running shoes Introduction Differences in spatiotemporal parameters as well as ground reaction forces (GRF) have been reported when comparing shod and barefoot running. It is also discussed whether barefoot running reduces injury rates (Murphy et al., 2013). Recent trends in shoe development therefore attempt to mimic the barefoot condition. It is speculated that running with so called minimalistic shoes (MS) also differs in above mentioned parameters and might influence performance when compared to running with traditional shoes (TS, Perl et al., 2012). Thus, we aimed to analyse spatiotemporal parameters, GRF and performance parameters while running in a new MS as compared to TS. Methods: Thirteen recreational runners (10 women, 3 men, 24 (SD 1.2) y, 1.68 (0.07) m, 62.8 (6.0) kg, training volume >30 km/week) participated in this randomized crossover-study. Participants were tested once with their TS and once with a MS (On Cloudsurfer, On AG, Zürich, Switzerland). Test order was randomized with a 6-week wash-out period in between and a 2- week run-in period (to familiarize runners with MS) prior to the MS test. For each participant, the lactate threshold was determined for either condition during an incremental running test on a treadmill. On a second test day spatiotemporal stride parameters and ground reaction forces were recorded at 80% IAT (10.0 ± 0.5 km/h, not different between conditions) and 95% IAT (11.8 ± 0.6 km/h) on a treadmill. On the same day, a 4 km all-out test was performed on an outdoor athletic track. Results: We found a likely higher peak vertical GRF during push-off (+5.7% [90% CI 1.3; 10.4], effect size (d)=0.5) at 95% IAT and a small possibly positive difference at 80% IAT (+2.2% [-3.5; 8.3], d=0.19). For spatiotemporal stride parameters and acceptance loads differences between conditions were possibly to likely trivial (d<0.14). Similarly, all performance parameters showed possibly to likely trivial effects (d<0.16). Only maximal blood lactate concentrations were very likely higher in the MS condition (+1.7 mmol/l [0.7; 2.8], d=1.0). Discussion: Running with the analysed MS did not lead to relevant changes in stride parameters or acceptance loads. This can be explained by the design of the shoe as the heel area has cushioning similar to TS. Increased peak vertical GRF can be attributed to the compressed, and then locked cushioning during push-off. This stronger push-off did not lead to altered performance as it was probably too small.